Determination of the Impacts of Urban-Planning of the Urban Land Area Using GIS Hotspot Analysis - Kucukpehlivan, Tuncay; Cetin, Mehmet; Aksoy, Talha; Kurkcuoglu, Muzeyyen Anil Senyel; Cabuk, Saye Nihan; Pekkan, Ozge Isik; Cabuk, Alper (Elsevier Sci Ltd, 2023)
Public investments are commonly linked with urban growth and change in points of interest (POI). This study aims to detect the changes in 5 POI categories within 250, 500, and 1000 m catchment areas around major public investments and transportation lines between 2008 and 2019 in Eskisehir city, Turkey. Due to the high number of POI data in the area, hot spot maps were produced for the target years with Kernel Density Estimation (KDE) method and subtracted with raster operation to create the POI differencing maps. The results revealed that establishing the tram line (ESTRAM) affected the emergence of POIs from 2008 to 2019, while no significant influence of other public investments on the POIs was detected in the city. Still, some investments, including Ataturk Culture and Convention Center, S,elalepark, the Zoo, and the City Hospital, had limited impacts on POIs. This research is expected to contribute to the prediction of the effects of public investments on the spatial and functional development processes and provide an analytical framework.
Cetin, Mehmet/0000-0002-8992-0289; Aksoy, Talha/0000-0001-8577-3990; Cetin, Mehmet/0000-0002-8992-0289;
Keywords: Point of Interest; Public Investment; Geographical Information Systems; Kernel Density Estimation